AMC based IP microwave technology - Weihe DONG; Xiaokun LI; Hongxu CHEN; Siyan ZHANG; Yiran SUN; Chuanyue YU (Dianxin kexue, 2020)
IP microwave technology is a new transmission technology,which uses IP technology to transmit data signals in the microwave field.It has the advantages of fast deployment rate,flexible installation,convenient transport and efficient data transmission,and has become a common ground wireless transmission system with large capacity.An environmental model of microwave transmission was proposed and discussed.The model used IP network as the return transmission,which was helpful for the development of general network of wireless access system.The prototype design of UHF band microwave/Internet protocol (IP) network interface was carried out,and the conversion of the three major functional modules in the network were described,to realize the broadband integrated services digital transmissions.The results show that the ground transmission signal (DTMB) can efficiently transmit on the IP network,and the monitoring/truncation of the microwave signal can significantly reduce the network throughput as needed.